Long-term safety of rituximab induced peripheral B-cell depletion in autoimmune neurological diseases - Memon, Anza B.; Javed, Adil; Caon, Christina; Srivastawa, Shitiz; Bao, Fen; Bernitsas, Evanthia; Chorostecki, Jessica; Tselis, Alexandros; Seraji-Bozorgzad, Navid; Khan, Omar (PLOS ONE, 2018)
Background B-cells play a pivotal role in several autoimmune diseases, including patients with immune-mediated neurological disorders (PIMND), such as neuromyelitis optica (NMO), multiple sclerosis (MS), and myasthenia gravis (MG). Targeting B-cells has been an effective approach in ameliorating both central and peripheral autoimmune diseases. However, there is a paucity of literature on the safety of continuous B-cell depletion over a long period of time. Objective The aim of this study was to examine the long-term safety, incidence of infections, and malignancies in subjects receiving continuous therapy with a B-cell depleting agent rituximab over at least 3 years or longer. Methods This was a retrospective study involving PIMND who received continuous cycles of rituximab infusions every 6 to 9 months for up to 7 years. The incidence of infection related adverse events (AE), serious adverse events (SAE), and malignancies were observed. Results There were a total of 32 AE and 4 SAE with rituximab treatment. The 3 SAE were noted after 9 cycles (48 months) and 1 SAE was observed after 11 cycles (60 months) of rituximab. There were no cases of Progressive multifocal leukoencephalopathy (PML) and malignancies observed throughout the treatment period. Rituximab was well tolerated without any serious infusion reactions. Also, rituximab was found to be beneficial in treating PIMND over a 7-year period. Conclusions This study demonstrates that long-term depletion of peripheral B-cells appears safe and efficacious in treating PIMND. Longer and larger prospective studies with rituximab are needed to carefully ascertain risks associated with chronic B-cell depletion, including malignancies. Recognizing that this is a small, retrospective study, such data nonetheless complement the growing literature documenting the safety and tolerability of B-cell depleting agents in neurological diseases.